MENINGKATKAN OMZET PENJUALAN MELALUI PENINGKATAN KUALITAS PRODUKSI TANDAN BUAH SEGAR DI PT. MAKMUR AGRO LESTARI - Darmansah, Darmansah; Cenderato, Cenderato (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
PT. Makmur Agro Lestari, Ketungau Hilir District, is one of the oil palm plantations in the Sintang Regency region, which also produces fresh fruit bunches (FFB) from its own plantations. Market FFB using sustainable and quality production methods so that the company's palm sales can increase with each harvest and each year. This type of research is qualitative. Data collection involved interviews, document research, and observations. The research subjects are property managers, administrative heads and employees. The researchers analyzed the results of the interviews based on the respondents' understanding of what was expressed. The data that has been compiled must be understood as a whole so that the researcher can grasp the experiences, issues, and dynamics that are actually occurring within the population being studied. Research results show that marketing of palm products always meets FFB's sales goals. The company has cooperated with customers to sell palm products to PT. ASL - POM Agency is one of the largest buyers of palm fruit in West Kalimantan. From the quality perspective of FFB. Makmur Agro Lestari Ketungau Hilir district harvests and sells selectively, so the quality and selling price are stable according to FFB's market price when sold to purchasing companies.